2002
DOI: 10.1007/s00256-002-0531-y
|View full text |Cite
|
Sign up to set email alerts
|

MRI of joint fluid in femoral head osteonecrosis

Abstract: The amount of joint fluid correlates well with the stage of ONFH. The amount of joint fluid does not correlate with IMP or bone marrow edema.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
7
0

Year Published

2009
2009
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 18 publications
(7 citation statements)
references
References 13 publications
0
7
0
Order By: Relevance
“…Exosomes released from mosquito cells infected with dengue virus were observed to have an effect on native C6/36 cells, which shows that the exosomes played a role in virus dissemination (Reyes-Ruiz et al, 2019). Exosomes secreted from dengue virus infected cells has been observed to carry LC3-phosphatidylethanolamine conjugates (LC3 II), which is an autophagy marker (Wu et al, 2016). However, further knowledge on plasma exosomes and their exact function in the transmission dengue virus is still lacking.…”
Section: Denguementioning
confidence: 99%
“…Exosomes released from mosquito cells infected with dengue virus were observed to have an effect on native C6/36 cells, which shows that the exosomes played a role in virus dissemination (Reyes-Ruiz et al, 2019). Exosomes secreted from dengue virus infected cells has been observed to carry LC3-phosphatidylethanolamine conjugates (LC3 II), which is an autophagy marker (Wu et al, 2016). However, further knowledge on plasma exosomes and their exact function in the transmission dengue virus is still lacking.…”
Section: Denguementioning
confidence: 99%
“…One of the dominant factors of ONFH is pain severity [29]. Moreover, severe pain is a key driver for ONFH treatment, and pain relief is a preliminary goal of therapy [30].…”
Section: Prace Oryginalnementioning
confidence: 99%
“…Among them, the box EMS is mainly used for stainless steel and silicon steel, and it is generally installed in the form of a single side, which can be installed on the inner arc side or the outer arc side, and it can be moved back and forth by hydraulic system, which is very convenient for changing the segment. [2] Wu et al [3] found that the stirring parameters of EMS in the second cooling zone had a significant effect on the equiaxed crystal ratio, central segregation, and white bright band of silicon steel continuous casting slabs. Song et al [4] investigated the turbulence, temperature field, and macroscopic solidification of steel in small billet continuous casting under S-EMS by establishing a 3D mathematical model.…”
Section: Introductionmentioning
confidence: 99%